RAISING THE ECOLOGICAL AWARENESS IN SAMUEL TAYLOR COLERIDGE'S POEM THE RHYME OF THE ANCIENT MARINER A SOCIOLOGICAL PERSPECTIVE - HARTIWI, WIWIK SRI (2011)
This study is aimed to show raising the ecological awareness in Samuel Taylor Coleridge's poem The Rhyme of the Ancient Mariner a sociological perspective. It is done by establishing two objectives: the first is analyzing the poem based on the sociological perspective. The second is analyzing the poem based on the structural analysis. This research is descriptive research. Type of data of the study is the lyrics of the poem from two data sources: primary and secondary. The primary data source is The Rhyme of the Ancient Mariner by Samuel Taylor Coleridge. While the secondary data sources are other materials taken from books, and internet relating to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the speaker, spoken to, setting, theme, imagery, figurative language, rhythm and meter related to each other and form the unity into good quality poem. Second, based on the sociological analysis, there is close relationship between the lyrics of the poem and the reality of England life that England need to raise the ecological awareness to reach the balancing life of human being between the natures and also respect to the other creation of God.